GAYA KEPENGARANGAN GODI SUWARNA DALAM KUMPULAN CERPEN MURANG-MARING - Taufik Rahayu (Badan Pengembangan dan Pembinaan Bahasa, 2017)
This research aims to reveal the style of author Godi Suwarna in the short stories collection buku Murang-Maring. In the universe of Sundanese literature, the Godi’s writing style is a new thing that contradicts the general style of Sundanese literature that is realism. Godi grew up in a rural area, and later as an adult continued in an urban environment. His short stories are the collaboration and mixing between the city and the village, traditional and modern. The ideas that are raised into his work are also mostly reconstruct the traditional stories that already exist, be it from folklore, pantun stories, wayang stories, fairy tales and so forth into a new, more modern form in accordance with the will of the author. Godi and his works are dissected by using expressive studies that focus the discussion to the collection of short stories Murang-Maring and the character of Godi himself. Based on the results of the research, Godi is an author who is upset with the surrounding social circumstances. The clash between rules and freedom also greatly influences Godi's self in his works. Godi's short story works are like a container for aspiration and criticism. In addition, the influence of wayang is very visible in the short stories, either from the stroytelling style or borrowing the characters with his nyeleneh and unique style.AbstrakRiset ini bertujuan untuk mengungkap gaya pengarang Godi Suwarna dalam buku kumpulan cerpen Murang-Maring. Di jagat kesusastraan Sunda, gaya mengarang Godi adalah hal baru yang bertolak belakang dari gaya umum sastra Sunda yang beraliran realis. Godi dibesarkan di lingkungan pedesaan, dan kemudian setelah dewasa berlanjut di lingkungan perkotaan. Cerpen-cerpennya adalah kolaborasi dan percampuran antara kota dan desa, tradisional dan modern. Ide-ide yang diangkat ke dalam karyanya pun kebanyakan merekonstruksi cerita-cerita tradisional yang sudah ada, baik itu dari foklor, cerita pantun, cerita wayang, dongeng, dan sebagainya ke dalam bentuk baru yang lebih modern sesuai dengan kehendak pengarang. Godi dan karyanya dibedah dengan memakai kajian ekspresif yang memfokuskan pembahasan kepada kumpulan cerpen Murang-Maring dan sosok Godi sendiri. Berdasarkan hasil penelitian, Godi termasuk pengarang yang gundah dengan keadaan sosial di sekitarnya. Benturan antara aturan dan kebebasan juga sangat memengaruhi diri Godi dalam karya-karyanya. Karya cerpen-cerpen Godi juga seperti wadah untuk menyalurkan aspirasi dan kritik. Selain itu, pengaruh wayang sangat kental terlihat dari cerpen-cerpennya, baik itu dari gaya penceritaannya maupun meminjam tokoh-tokoh dengan gayanya yang nyeleneh dan khas.